Concussions in the National Basketball Association: An Analysis from 1999-2018. Issue 7 (29th July 2019) - Okoroha, Kelechi; Patel, Bhavik H.; Lu, Yining; Idarraga, Alexander J.; Forsythe, Brian
Objectives: Several studies have examined the incidence and effects of concussions in professional football, baseball, and hockey, but there has been limited evaluation of the effects of concussions in National Basketball Association (NBA) players. This study aims to evaluate the epidemiologic trends of concussions, as well as the effects of concussions on in-game performance, in NBA players. Methods: Publicly available records were searched to include all players who sustained an in-game concussion while playing in the NBA from the beginning of the 1999 NBA season to the conclusion of the 2018 season. For each player the following variables were collected: date of injury, number of days and games missed before returning to game play, player efficiency rating (PER) in the season of injury, the season preceding the injury, and the season following the injury, position of the injured player, and the incidence of multiple concussions for a single player. Concussion trends before and after the institution of the NBA Concussion Protocol were calculated, as well as the effects on PER after return to play. Results: From the start of the 1999 season to the end of the 2018 season, 185 basketball-related concussions were incurred across 149 NBA players. All players were able to return to play following a first-time concussion after missing an average of 7.7 days and 3.5 games. The NBA Concussion Protocol was instituted ahead of the 2011-2012 season, prior to which there were 5.7 concussions recorded/season, with an average of 6.7 days and 3.0 games missed per first-time concussion. Following the institution of the concussion protocol, there were approximately 11 more concussions recorded/season (16.7 vs. 5.7, P = 0.007), with 1.7 more days missed (8.4 vs. 6.7, P = 0.27) and 0.9 more games missed (3.9 vs. 3.0, P = 0.24) per concussion, compared to prior seasons. Of the 149 players who suffered concussions, 27 were concussed multiple times (18.1%). There was no difference found in the incidence of recurrent concussions within the same season before vs. after the institution of the concussion protocol (4 vs. 5, P > 0.05). PER was almost identical for concussed players in the season prior to the injury, the season in which the injury occurred, and the season following the injury (13.93 vs. 13.94 vs. 13.91, P = 0.998). Conclusion: There has been a significant increase in the incidence of concussions in the NBA player following the institution of a league-wide concussion protocol. This likely reflects more accurate reporting secondary to advances in player education, medical knowledge, national media coverage, and standardized testing protocols. Despite this increase in reported concussions, the amount of time missed following injury has remained relatively constant. Player performance as reported by PER was not significantly affected by sustaining a concussion. Figure I. Incidence of concussions per NBA season from 1999 to 2018, with subsequent games missed by the injured player. The NBA Concussion protocol was instituted prior to the start of the 11-12 season. In the studied time frame, there were as few as two concussions/season, in both 02-03 and 03-04, and as many as 29 concussions/season in 17-18. Average games missed ranged from one game/concussion, in 03-04, to 6.3 games/concussion in 10-11. Season Concussions, n Games Missed, Mean ± SD Days Missed, Mean ± SD Repeat Concussions, n Concussions by Position Point Guard Shooting Guard Small Forward Power Forward Center 99-00 4 1.3 ± 1.3 3.0 ± 0.8 0 0 2 0 1 1 00-01 4 3.0 ± 1.4 7.0 ± 4.4 0 1 0 2 1 0 01-02 7 1.4 ± 0.8 4.6 ± 4.2 1 3 0 1 3 0 02-03 2 2.5 ± 1.5 4.5 ± 2.5 0 0 1 0 0 1 03-04 2 1.0 ± 0 * 3.0 ± 0.0 * 0 0 1 0 1 0 04-05 4 4.8 ± 4.8 9.0 ± 7.9 0 0 1 2 0 1 05-06 9 1.5 ± 0.8 3.0 ± 1.5 2 3 1 2 3 0 06-07 4 1.5 ± 0.5 4.5 ± 1.5 0 2 0 1 0 1 07-08 8 3.1 ± 2.1 7.0 ± 5.1 0 1 1 2 2 2 08-09 10 1.8 ± 0.4 3.8 ± 1.1 1 0 0 3 5 2 09-10 5 3.7 ± 1.3 9.3 ± 3.3 0 1 2 1 1 0 10-11 9 6.3 ± 7.4 13.6 ± 14.8 0 1 4 2 2 0 Before Concussion protocol, aggregate 68 3.0 ± 3.6 6.7 ± 7.6 4 (5.9%) 12 (17.6%) 13 (19.1%) 16 (23.5%) 19 (27.9%) 8 (11.8%) 1H2 18 4.2 ± 5.2 8.7 ± 0.2 0 3 1 1 1 6 3S-13 14 5.8 ± 4.5 12.9 ± 10.9 0 2 2 3 3 4 4 2.5 ± 0.5 5.0 ± 2.0 0 1 0 0 2 1 14-15 14 2.8 ± 2.3 6.3 ± 5.6 0 0 5 6 1 2 IKS 18 2.8 ± 1.7 6.3 ± 3.0 1 4 5 1 6 2 JH7 20 3.9 ± 5.5 8.2 ± 10.2 1 5 3 5 2 5 37-10 29 3.8 ± 4.1 8.7 ± 9.5 3 4 7 3 8 7 After Concussion protocol, aggregate 117 3.9 ± 4.4 8.4 ± 9.1 5 (4.3%) 19 (16.2%) 23 (19.7%) 22 (18.8%) 26 (22.2%) 27 (23.1%) Overall from 99-00 to 17-18 185 3.5 ± 4.1 7.7 ± 8.6 9 (4.9%) 31 (16.8%) 36 (19.5%) 38 (20.5%) 45 (24.3%) 35 (18.9%) Summary of NBA concussion incidence and return to play times stratified by season from the 99-00 to 17-18 seasons. Incidence data includes all basketball related concussion within the studied timeframe. Return to play data includes only first-time concussions, and excludes pre-season or post-season injuries, players whose recovery overlapped with the last day of the regular season, and players who suffered concussions concomitantly with other injuries, due to concerns that these parameters would artificially affect the number of games missed. *There were only two concussions in this season, and one was excluded because it was a pre-season injury.